Transcoronary pacing to assess myocardial viability prior to percutaneous coronary intervention: Pilot study to assess feasibility. Issue 2 (16th October 2017) - O'Neill, James; Hogarth, Andrew J.; Pearson, Ian; Law, Hannah; Bowes, Robert; Kidambi, Ananth; Wheatcroft, Stephen; Sivananthan, U. Mohanaraj; Tayebjee, Muzahir H.
Abstract: Background: The assessment of myocardial viability is crucial before percutaneous coronary intervention (PCI) is carried out to ensure that the patient will gain benefit. Trans‐coronary pacing (TCP) has previously been used to pace myocardium but may also provide information on myocardial viability. Methods: Patients with a single, significant coronary stenosis requiring PCI were recruited. They underwent a cardiac MRI to assess myocardial viability. Prior to PCI, a coronary guidewire was used to measure pacing threshold, impedance, and R‐wave amplitude in different myocardial segments to determine any association between the electrical parameters and myocardial viability. Results: Eight patients were recruited and six patients underwent intervention. Pacing sensitivity did not demonstrate statistically significant differences between normal and scarred myocardium. Impedance demonstrated a mean of 304.8 ± 74.0 Ω in normal myocardium (NM), 244.1 ± 66.6 Ω in <50% myocardial scar (MS), and 222.3 ± 33.8 Ω in ≥50% MS. Pacing threshold demonstrated a mean of 1.960 ± 1.226 V in NM, 5.009 ± 2.773 V in <50% MS, and 3.950 ± 0.883 V in ≥50% MS. For both impedance and threshold, there was a significant difference among the groups ( P = 0.12 and P = 0.002, respectively), and post hoc Tukey's pairwise comparison demonstrated significant differences between NM and scarred myocardium. No significant differences were found between <50% MS and ≥50% MS. Conclusions: Impedance and pacing threshold, measured during TCP, can be used to differentiate between normal myocardium and scarred myocardium. Further research is needed to determine whether TCP can discriminate between viable and nonviable myocardium.